Analisis Pemborosan Waktu Pelayanan Dengan Metode Lean Healthcare dan Root Cause Analysis 5 Why (Studi Kasus: Poli Saraf RSUD dr. Darsono Pacitan) - Prasetyo Mukti; Rochmoeljati Rochmoeljati (LPPM Institut Pendidikan Nusantara Global, 2026)
Healthcare services demand speed, accuracy, and quality to meet expectations and increase patient satisfaction. However, in practice, waste is still frequently encountered in service flows, such as long queues, long waiting times, data recording errors, and inefficient manual activities. This situation also occurs at the Neurology Clinic at dr. Darsono Pacitan Regional Hospital, the main referral hospital in Pacitan Regency. This study aims to identify forms of waste in services at the Neurology Clinic and propose improvements to increase service efficiency. The method used is the Lean Healthcare approach with the assistance of Root Cause Analysis (RCA) and the 5 Whys technique to identify the root causes of problems. The analysis using BPM showed that the initial service lead time was 127 minutes. After implementing the improvement recommendations, non-value-added activities were completely eliminated, reducing the lead time to 68 minutes, equivalent to a 46.5% reduction in time. The improvement recommendations focused on increasing the efficiency of neurology services through human resource optimization, work system organization, implementation of 5S, utilization of information technology, digitization of medical records, and involvement of medical personnel in improving service quality.